A diagnostic test in composition for fourth year high school students - Geconcillo, Ofelia (Sindiong) 1922- ([Quezon City publisher not identified], 1965)
A more objective measuring instrument in composition ability to supplement theme rating is deemed needed to be devised so that English teachers will have a fairer basis of assigning grades in composition. This is because the evaluation of theme writing is subjective though it is the best way of measuring writing. The author believes that the rating of which cannot be wholly reliable. The diagnostic test provided in the study is an attempt to pave the way for other similarly constructed tests which will measure students' knowledge, abilities and understandings of the elements essential to good writing.
Thesis (Master of Arts in Teaching)--University of the Philippines.
Keywords: English language -- Composition and exercises